Assessment of bank regulations and profitability of commercial banks listed in Nairobi Securities Exchange in Kenya - Mwende Magdalene (Meru Magdalene Mwende, 2023)
The most heavily regulated workplace in the world is that of commercial banks, which is why theoretical analysis of banking rules is ongoing. Every bank in Kenya is required to abide by the laws and regulations set forth by the Central Bank of Kenya. Such rules and regulations are crucial because they aim to safeguard the interests of depositors, creditors, and investors while also fostering market integrity. Kenyan commercial banks have experienced issues with their performance, including a drop in earnings, being placed in receivership, and a significant amount of nonperforming loans. This has occurred following the amendment of the CBK Act's rules and regulations (Chapter 491 of Kenyan law). Therefore, the purpose of this study was to EVALUATE the impact of bank rules on the financial performance of commercial banks listed on Kenya's Nairobi Securities Exchange. This study specifically looked at the effects of capital adequacy, credit risk, and liquidity management requirements on the profitability of commercial banks listed on the Nairobi Securities Exchange. This study was directed by the hypotheses of the public interest in regulation, the demand for liquidity, and the balanced portfolio. This study used a descriptive research strategy. Managers from the risk and compliance, credit, and finance departments of the eleven commercial banks listed on the NSE made up the population of interest. Both primary and secondary resources were used to compile this study's findings. To improve the validity and reliability of the research instrument as a whole, a pilot study was conducted. The investigation produced both qualitative and quantitative pieces of information. The researcher also made use of the findings from multiple regression analysis to highlight the significance of capital adequacy management, liquidity management, and credit risk management techniques in ensuring that banking operations run repayment smoothly. A sufficient amount of cash helps to limit risks such as defaulting on the of a loan. The study concludes that commercial banks' profits are positively correlated with capital adequacy regulations. The study also found that commercial bank profits are positively correlated with regulations governing liquidity management, which in turn have a beneficial impact on bank profits. The study comes to the conclusion that the reform of CBK's prudential regulations and guidelines encouraged commercial banks with NSE listings to perform well. Therefore, it is crucial for banks to keep making sure they have enough capital in place. Strong credit risk management practices should be developed by banks; these practices should include assessments of creditworthiness, investment viability, and credit insurance measures, and bank management should ensure that they retain high levels of liquidity.
A project submitted in partial fulfillment of the requirements for conferment of the Degree of Masters of Business Administration of Meru University of Science and Technology.